Effects of different decision-making factors of driving cessation after acquired brain injury on occupational participation: A pilot study - Nasu, Satonori; Ishibashi, Yu; Kobayashi, Ryuji; Ikuta, Junichi (Japanese Occupational Therapy Research, 2024)
This study examined the effects of different decision-making factors on driving cessation after acquired brain injury. Occupational participation was measured through a pilot study using a questionnaire. The subjects were 26 acquired brain injury patients divided into two groups: those who voluntarily decided to stop driving (self-decision group) and those forced to do so by their healthcare providers or family members (third-party decision group); the two groups were then compared by occupational therapists. The results showed that the third-party-determined group significantly decreased their scores scores for “things one wants to do” and “things one needs to do,” and that the inability to drive tended to cause inconvenience in many of the activities they performed daily. The results suggest that driving cessation after acquired brain injury may affect subsequent occupational participation differently depending on the decision-making factors.